2011
DOI: 10.1093/sp/jxr006
|View full text |Cite
|
Sign up to set email alerts
|

Do Family Policy Regimes Matter for Children's Well-Being?

Abstract: Researchers have studied the impact of different welfare state regimes, and particularly family policy regimes, on gender equality. Very little research has been conducted, however, on the association between different family policy regimes and children's well-being. This article explores how the different family policy regimes of twenty OECD countries relate to children's well-being in the areas of child poverty, child mortality, and educational attainment and achievement. We focus specifically on three famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 46 publications
0
32
0
1
Order By: Relevance
“…Five studies use a health inequality perspective, examining inequalities by socioeconomic position/status, type of mother (lone vs. coupled), education and income. The studies have been classified according to main type of policy area: family [15,16,56-59], pensions [17,59-61], economic assistance and unemployment benefits [58,62,63] and access to health care [64-66]. Two articles cover several policy areas [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies use a health inequality perspective, examining inequalities by socioeconomic position/status, type of mother (lone vs. coupled), education and income. The studies have been classified according to main type of policy area: family [15,16,56-59], pensions [17,59-61], economic assistance and unemployment benefits [58,62,63] and access to health care [64-66]. Two articles cover several policy areas [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…The family is the most proximate social unit for children, and the effect on children’s well‐being of high degrees of family social capital has been established in numerous studies (1,2,13). The tax‐funded support that is available to all families in Sweden, such as child health services and parental education, continue to be a central health promotion strategy (22).…”
Section: Discussionmentioning
confidence: 99%
“…The overall conclusion from a review was, for example, that having an engaged father benefits both psychological and physical aspects of health among children of both sexes [25]. It has also been found that generous parental leave policies associate with physical aspects of health such as increased birth weight, decreased premature birth, and decreased mortality among infants at the ecological level [36], that dual-earner regimes offering parental leave to both parents have lower levels of child poverty and child mortality [37], and that both maternity leave [38] and paternity leave [39] have positive effects on length of breastfeeding, and child mortality.…”
Section: Discussionmentioning
confidence: 99%